Emerging role of (18)F-fluorodeoxyglucose positron emission tomography for guiding management of hepatocellular carcinoma - Lee, Sang Mi (World J Gastroenterol, 2019)
Hepatocellular carcinoma (HCC) is one of major causes of cancer mortality worldwide. For decades, (18)F-fluorodeoxyglucose (FDG) positron emission tomography (PET) has been widely used for staging, predicting prognosis, and detecting cancer recurrence in various types of malignant diseases. Due to low sensitivity of FDG PET for detecting intrahepatic HCC lesions, the clinical value of FDG PET in HCC patients has been limited. However, recent studies with diverse analytic methods have shown that FDG PET has promising role in aiding management of HCC patients. In this review, we will discuss the clinical role of FDG PET for staging, predicting prognosis, and evaluating treatment response in HCC. Further, we will focus on recent clinical studies regarding implication of volumetric FDG PET parameters, the significance of FDG uptake in HCC for selecting treatment and predicting treatment response, and the use of radiomics of FDG PET in HCC.